Role of endothelial NAD+ deficiency in age-related vascular dysfunction - Csiszar Anna (AMERICAN JOURNAL OF PHYSIOLOGY: HEART AND CIRCULATORY PHYSIOLOGY, 2019)
Age-related alterations in endothelium and the resulting vascular dysfunction critically contribute to a range of pathological conditions associated with old age. To rationally develop therapies that improve vascular health and thereby increase health span and lifespan in older adults, it will be essential to understand the cellular and molecular mechanisms contributing to vascular aging. Pre-clinical studies in model organisms demonstrate that NAD+ availability decreases with age in multiple tissues and that supplemental NAD+ precursors can ameliorate many age-related cellular impairments. Here we provide a comprehensive overview of NAD+ dependent pathways (including the NAD+ utilizing sirtuins and poly (ADP-ribose) polymerase enzymes) and the potential consequences of endothelial NAD+ deficiency in vascular aging. The multifaceted vasoprotective effects of treatments that reverse the age-related decline in cellular NAD+ levels are discussed. The preventive and therapeutic potential of NAD+ intermediates as effective, clinically relevant interventions in older adults at risk for ischemic heart disease, vascular cognitive impairment and other common geriatric conditions and diseases that involve vascular pathologies (e.g. sarcopenia, frailty) is critically discussed. We propose that NAD+ precursors (e.g., nicotinamide riboside, nicotinamide mononucleotide, niacin) should be considered as a critical component of combination therapies to slow the vascular aging process and increase cardiovascular health span.